The use of B*- trees to create and calculate OLAP cubes using a combinatorial algorithm - Горбань, Гліб Валентинович (Technology audit and production reserves, 2013)
The paper considers the approach to building a multidimensional OLAP cube in the form of B*- tree structure, and the algorithm of its creation, using a combinatorial approach to the calculation of aggregate values of the cube. The main objective of research is to develop the methods of effective materialization of OLAP-cubes for further integration with the models and methods of Data Mining. The proposed storage structure of multidimensional data allows solving the problem of data irrelevance; it is suitable for both dense and sparse cubes, and the proposed algorithm allows efficient calculation of aggregate values of the OLAP cube. The research results can be applied in various fields, which use database management systems, as well as in decision support systems, using the methods of business intelligence.